Comparing corporate governance practices of state-owned enterprises (SOEs) in South Africa and Singapore - Adebayo, Adeyemi; Ackers, Barry (Journal of Accounting and Investment, 2022)
Research aims: This paper undertakes a cross-country comparative analysis of corporate governance of state-owned enterprises (SOEs) in South Africa and Singapore, two countries using two different models for organising SOEs, with specific reference to agreement with the themes identified in the World Bank’s Framework for good Corporate Governance practices for SOEs. The aim of this paper is to identify differences and similarities in practice and to document how the states have fared using different models.Design/Methodology/Approach: The paper deploys a pragmatic mixed methods approach conducted in two phases, to understand the practices utilised by South African and Singaporean SOEs. The data emerging from these two phases, were compared to the Framework for good Corporate Governance practices for SOEs issued by the World Bank.Research findings: Findings suggest although South African SOEs have good corporate governance practices in place, Singaporean SOEs are better organised and governed compared with South African SOEsTheoretical contribution/Originality: This paper contributes to the scholarly discourse on SOEs in by expanding the discourse on public sector entrepreneurship and opening up new debates and research areas corporate governance of SOEs.